Efficient technologies Walling low-rise buildings - Tonkacheev, G.; Klys, M. (Ways to Improve Construction Efficiency, 2015)
Analysis options wall erection used for the construction of low-rise buildings. Comparison of different options technology wall erection of technical and economic parameters. Advantages of each option identified and considered.